Fenologi Fase Pembungaan dan Perbuahan serta Produksi Polen pada Tanaman Kacang Panjang Kultivar Sabrina: Phenology of Flowering and Fruiting Phases, and Pollen Production in Yardlong Bean Cultivar Sabrina - Nurul Fadhila Rizkyma; Nunik Sri Ariyanti; Dorly (Departemen Biologi, Institut Pertanian Bogor, 2023)
Yardlong beans (Vigna unguiculata subsp. sesquipedalis (L.) Verdc.) is a vegetable source of vitamins and minerals which are quite widely cultivated in Indonesia. Phenology study the phases that occur in a plant that is provides benefits in agriculture, but information on the phenology of legumes crops in Indonesia is still scarce. This study aims to observe the reproductive phenology and pollen production of the yardlong bean cultivar Sabrina. A phenological study was carried on 7 plants to obtain information on the timing and duration of the reproductive period, inflorescence and fruiting phases, peak flowering time, and flower biology. Pollen production was observed in 5 samples of flowers. Pollen microscopic preparations were made using the acetolysis method. The results showed that the flowering and fruiting phases took 21-29 days; including flower initiation phase 7-10 days, small bud phase 1day, large bud phase 1 day, anthesis phase 1-2 days, and fruit development phase 11-15 days. Flower initiation occurred 36 days after planting (DAP), and flower blooming occurred 49 DAP. The peak of flowering occurred at 56-62 DAP. The flowers of the Sabrina cultivar have purplish-white corollas, producing about 276±23.58 pollen/anther.